Centella asiatica enhances diabetic wound healing by decreasing macrophage-driven inflammation via the AKT/MAPK/NF-κB pathway - Xiao, Fugang; Li, Qin; Zeng, Wenwen; Tang, Botao; Chen, Qingqing; Wu, Chengjie; Duan, Zixiao; Chen, Huan; Rui, Shunli; Liu, Bin (Frontiers in Pharmacology, 2025)
BackgroundDiabetic foot ulcers (DFU) pose a major global healthcare challenge, necessitating novel therapeutic strategies. Although Centella asiatica has demonstrated pharmacological potential, its role in diabetic wound healing remains unclear. This study aims to investigate the mechanisms through which Centella asiatica promotes wound healing under diabetic conditions.MethodsA systematic pharmacological approach was employed to identify potential targets of Centella asiatica in DFU. In vitro experiments used Raw264.7 macrophages stimulated by advanced glycation end products (AGEs). For in vivo validation, a diabetic mouse model was established using high-fat diet and streptozotocin (STZ). Full-thickness skin wounds were topically treated with Centella asiatica at concentrations of 200 μg/cm2 and 300 μg/cm2.ResultsCentella asiatica significantly suppressed AGE-induced nitric oxide (NO) overproduction and downregulated inducible nitric oxide synthase (iNOS) and pro-inflammatory cytokines in Raw264.7 cells. It also promoted anti-inflammatory factor expression. Mechanistically, it activated the AKT/MAPK/NF-κB pathway. In diabetic mice, Centella asiatica accelerated wound closure, with the most effective dose observed at 200 μg/cm2.ConclusionThis study demonstrates that Centella asiatica facilitates diabetic wound healing through anti-inflammatory mechanisms involving the AKT/MAPK/NF-κB pathway. These findings provide mechanistic support for the potential integration of Centella asiatica into DFU management.